Continuous infusion of ceftazidime for patients with breast cancer and multiple myeloma receiving high-dose chemotherapy and peripheral blood stem cell transplantation - Egerer, Gerlinde; Goldschmidt, Hartmut; Hensel, Manfred; Harter, Christoph; Schneeweiss, Andreas; Ehrhard, Ingrid; Bastert, Gunther; Ho, Anthony Dick (Bone marrow transplantation, 2002)
This prospective study was performed to examine the safety and efficacy of a continuous infusion of ceftazidime in patients who developed febrile neutropenia after high-dose chemotherapy (HDCT) and autologous peripheral blood stem cell transplantation (PBSCT) and to determine if the underlying disease represents a risk factor for infectious complications. From September 1995 to May 2000, 55 patients with breast cancer (BC, group I, 54 females, one male) and 32 patients with multiple myeloma (MM, group II, 10 female, 22 male) were included in this study. The febrile patients received a 2 g intravenous bolus of ceftazidime, followed by a 4 g continuous infusion over 24 h using a portable infusion pump. If the fever persisted for 72 h a glycopeptide antibiotic was added. The median age was 42 years (range 22-59) in group I and 52 years (range 35-63) in group II. Thirty-five BC patients (64%) and 20 MM patients (63%) responded to the monotherapy with ceftazidime. After addition of a glycopeptide antibiotic, an additional 11 BC patients vs 10 MM patients became afebrile. The causes of fever in group I were fever of unknown origin (FUO) in 49 patients, microbiologically documented infection (MDI) in five patients, and clinically documented infection (CDI) in one patient. The causes of fever in group II were FUO in 22 patients, MDI in eight patients and CDI in two patients. Forty-one febrile episodes in BC patients (75%) and 22 episodes in the MM patients (69%) were successfully managed by out-patient treatment, resulting in a saving of an average of 20 days of inpatient care. Significantly more episodes of MDI and CDI occurred in patients with MM (P = 0.05). The results indicate that BC and MM patients with febrile neutropenia after HDCT and PBSCT can be treated as outpatients with close monitoring to ensure safety. This approach represents a better use of health care resources.